Beating about the bush [compact disc, unabridged] - Beaton, M. C. (Beaton, M. C. Agatha Raisin mystery., 2019)
One of Private Detective Agatha Raisin's many quirks was her tendency to exclaim, every time she drove along a motorway bordered by dense woodland, 'What a good place to dump a body!' Yet she's clearly not the only one to think so. The police realize this after poor, elderly Mrs. Dunwiddy is found dead in the scrub by the road leading out of Mircester. Agatha digs into the case, facing off with everyone from secretive factory bosses to Russian officials as she wades deeper into the mystery surrounding the killing. And as if things weren't complicated enough, Agatha finds herself grappling with intensifying feelings for her friend and occasional lover, Sir Charles Fraith. Will Agatha get her man at last? Or will the killer get her first?